How Do Prospective Elementary School Teachers Respond to Students' Mathematical Thinking? - Sunwoo Jin; JeongSuk Pang (Korea Society of Educational Studies in Mathematics, 2020)
Although the ability to respond to students' mathematical thinking is important among teachers' professional noticing, there has been a lack of research investigating such ability among Korean teachers. This study surveyed 95 prospective elementary school teachers with an aim to investigate their responding ability with five sub-components. A written assessment for this study was developed on the basis of students' solution strategies regarding four operations (addition, subtraction, multiplication, and division) of whole numbers. The results of this study showed that many teachers were able to identify the core mathematical elements in the student's strategy, interpret the student's strategy by using mathematical concepts and terms, and suggest an appropriate teaching method. However, some prospective teachers tended to pose inappropriate problems or provide superficial teaching methods in response to the student's mathematical thinking. It was unusual for them to anticipate the student's future strategies. Based on the obtained results, this study is expected to suggest the aspects that are further needed for prospective teachers to promote their ability to respond to students' mathematical thinking.